Resin Coaster Business Innovation Through Design Thinking - Utomo, Connie Wijaya; Wardaya, Marina (Universitas Ciputra, 2023)
The purpose of this study is to establish innovations for an arts & crafts business in the form of resin coasters through solving a common problem from the target users, which is work stress. This research used a design thinking method to yield solutions and the innovations for the product. The research method used in this study is both qualitative and quantitative method through questionnaires with Google Form. The questions given were answered using a scaling system called Likert scale (1 - 5). For the qualitative data, literature review and opinions from respondents were asked through the questionnaire. Questionnaires were done twice, for empathize and testing steps, and both have passed validity and reliability tests. This study used the technique of purposive sampling, with a total of 30 respondents having certain criterias (not required to pass all) such as: Indonesian people, 18-40 years old, coffee/tea/other drinkers, office/desk-job workers, or students. The result of the design thinking method suggested that innovations by adding motivational quotes and adding unique designs/color (thermochromic) is suitable for developing the resin coaster product. It concludes that the prototype made has met the wants and needs of the target users, although there is still some room for improvements as mentioned by the respondents. Further research in looping the design thinking method from step 1 to 5 is needed to create the best version of the prototype that is ready to be sold to the market.